Physiological and transcriptome analysis of changes in endogenous hormone contents and related synthesis and signaling genes during the heat stress in garlic (Allium sativum L.) - Qing-qing Yang; Ji-De Fan; Can-yu Liu; Yong-qiang Zhao; Zhi-sheng Xu; Xin-juan Lu; Jie Ge; Bi-wei Zhang; Meng-qian Li; Yan Yang; Feng Yang (BMC Plant Biology)
Abstract High-temperature stress severely limits the growth, development, yield, and quality of garlic (Allium sativum L.), but the role of hormone signaling in its heat stress response remains unclear. This study examined changes in seven plant hormones and the expression of related genes in garlic leaves (‘Xusuan No. 6’) under heat stress (38 °C for 0, 2, 4, and 24 h). Growth-promoting hormones, auxin and gibberellic acid, significantly decreased within 2 h of heat stress, while stress-response hormones, including abscisic acid, jasmonic acid, salicylic acid, and ethylene, increased. KEGG pathway analysis revealed significant changes in genes related to hormone biosynthesis and signal transduction, such as NCED and PYR/PYL in the ABA pathway, LOX and OPR in JA biosynthesis, AUX and ARF in IAA signaling, and ERT and ERF in ethylene signaling. A protein–protein interaction network identified 15 hub genes potentially coordinating hormone regulation under heat stress. These findings provide a basis for functional validation of key hormone-related genes in the garlic heat-stress response and suggest potential genetic targets for the development of heat-tolerant garlic varieties.